The relationship between heart functions and anemia in patients with end-stage renal disease receiving hemodialysis - Omar, Timor; Çağdaş, Metin; Artaç, İnanç; Karakayalı, Muammer; İliş, Doğan; Arslan, Ayça; Karabağ, Yavuz; Yesin, Mahmut; Avcı, Mustafa; Rencüzoğulları, İbrahim (The European Research Journal, 2024)
Objective: We investigated the relationship between anemia and cardiac functions by conventional and speckle-tracking echocardiography (STE) in patients with end-stage renal disease (ESRD) receiving hemodialysis. Methods: One hundred six patients with ESRD receiving hemodialysis were included in this cross-sectional study. The conventional echocardiography and STE findings were compared between the patients with and without anemia. In addition, a comparison of the findings between the ESRD patients and healthy controls consisting of 68 participants was conducted. Results: Compared to healthy controls, ESRD patients had lower left ventricular ejection fraction (LVEF), left ventricular global longitudinal strain (LVGLS), and left atrial reservoir strain (LASr) [53% (48-57) vs. 65% (62-68), -15.2 (-16.9˗ -13.6) vs. -19.7 (-16.9˗ -13.6), and -21.9 (-29.5˗ -15.3) vs. -29.9 (-35.3˗ -22.8), respectively, P-value